PENYULUHAN HUKUM JAMINAN KEBENDAAN DI KANTOR KECAMATAN SERPONG, TANGERANG SELATAN - Ratnawati, Elfrida; Arsawan, I Gede Yudi; Pratomo, Abdurracman Satrio; Budhianti, Meta Indah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The legal counseling on material guarantees at the Serpong District Office, South Tangerang aims to provide understanding, information and legal knowledge about how people can guarantee their movable and immovable objects at bank and non-bank financing institutions in the form of general and special guarantees (mortgage, pawn, fiduciary, Dependents, Warehouse Receipts and Individual Guarantees or Bortoght). This Community Service (PKM) uses an implementation method in the form of outreach activities and discussions with the village head and sub-district head. This PKM activity provides benefits to the village head and sub-district head which will later be shared with the surrounding community by increasing understanding of guarantee law at the Serpong District Office, South Tangerang. Through discussion activities between the service team and the village head and sub-district head, it was discovered that many did not understand material guarantees. Therefore, it is necessary to provide knowledge and supporting knowledge to provide knowledge to the public about the rules that apply to each material guarantee.Keywords: Guarantee, Materials, Tangerang-South